HUBUNGAN DUKUNGAN SOSIAL DENGAN RESILIENSILANSIA DI DAERAH RISIKO TINGGI BANJIR KELURAHANKOTABARU KECAMATAN SERANG - Ghea Andriani (2023)
Disasters are unforeseen circumstances that may cause damage, death, or loss of property. Social support is one of the supports for the elderly when facing various difficulties. This study aims to determine the relationship between social support and the resilience of the elderly in high-risk flood areas, Kotabaru Village, Serang District. This study used a cross-sectional method with a quota sampling technique for 147 respondents in the Kotabaru Village, Serang District. Data collection in this study used two scales, namely the social support scale and the resilience scale. The social support and resilience scale consists of 22 items with a reliability coefficient of 0.944. The results of the study were tested using the Chi-Square Test. The results of the hypothesis test obtained a significance level of p = 0.000 (p <0.05). This shows that there is a significant relationship between social support and resilience. So it can be concluded that the greater the social support received by the elderly, the better their resilience. Vice versa, the less social support received, the lower the resilience.